Turkey : Do Job Training Programs Help People Find Jobs? - World Bank (Washington, DC, 2015)
Jobs are critical to ending the cycle of poverty because they give people the opportunity to support themselves and their families. Policymakers focused on helping people move into the workforce often turn to vocational training and retraining programs. But do these actually improve people s chances of finding work? Do the jobs pay enough to justify the costs of the training programs? Who provides the best courses - private firms or state organizations? Policymakers and researchers are looking for answers to these questions and more in order to understand how to create programs that work best. In Turkey, researchers from the World Bank worked with the government to evaluate the impact of the Turkish National Employment Agencys (ISKUR) vocational training program to reduce unemployment. Based on the results, the government increased courses by private providers and took steps to ensure the quality of the offerings. The government also added job search assistance, improved employment counseling, increased efforts to enroll beneficiaries of social assistance programs who are able to work, and offered incentives to those beneficiaries of social assistance who actively search for a job after the course.